Multicomponent porphyrins as platforms for applications with nanomaterials and in DSSCs - MEINDL, ALINA (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
The aim of this research was to investigate different multicomponent porphyrin systems. Special interest was put on donor-acceptor units, the specific molecular arrangement of units within the multicomponent systems as well as distinctive electronic properties such as those in conjugated and isolating systems. Contemporary applications in optics, medicine, solar cells or material science are increasingly reliant on unsymmetrically substituted porphyrins. Due to their widespread uses and rise in demand, a comparative analysis of synthetic strategies for meso-substituted porphyrins was undertaken and the synthesis of different series of so-called A 2 BC push-pull porphyrins was explored. The synthetic pathways used were applied to both 5,15-substituted and 5,10-substituted porphyrins, showcasing their flexibility and adaptability for different needs. Furthermore, the linkage of an electronically isolating unit to a porphyrin was explored. Therefore, the cubane unit was chosen as an example of a non-conjugated hydrocarbon linker. One of the major objectives of this study was to gain deeper insights into the cubane C-C coupling chemistry, with a special focus on the synthesis of directly linked cubane-porphyrin systems and multi-porphyrin arrays with cubane as scaffold linker. Besides electronically isolated systems also conjugated systems were investigated. Here, especially the distinct interaction of various porphyrin materials with different nanomaterials was of interest. One part involved the generation of synthetic methodologies for porphyrin-based supramolecular tectons for surface studies. The study aimed to generate porphyrins with directional anchoring groups with a special focus on organometallic coupling reactions for the introduction of benzoic acid moieties as anchor groups. Furthermore, interfacial charge transfer studies with the push-pull porphyrins ,developed above, and nanomaterials were undertaken. Another interaction was explored through the synthesis of pyridine-substituted Pd porphyrins for their use in Metal-organic Frameworks. Besides, to probe non-covalent interactions of various porphyrin systems with nanomaterials, also covalently linked porphyrins were investigated. Therefore, metal complexes of the 5-(4-ethynylphenyl)-10,20-diphenylporphyrin were synthesised to covalently link to the surface of an electrode. Finally, the synthesis of bisanthracene-substituted porphyrins was attempted. These porphyrins are of interest for optoelectronic devices as they represent a class of highly conjugated systems which are electronically coupled and possess a large bathochromic shift in their absorption spectra.
APPROVED
Keywords: porphyrinoids; sensitizers; multicomponent systems; synthetic methods